2007
DOI: 10.1159/000107547
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of <i>N</i>-n-butyl Haloperidol Iodide on Myocardial Ischemia-Reperfusion Injury in Rats by Inhibiting Egr-1 Overexpression

Abstract: Aims: Our previous studies have shown that N-n-butyl haloperidol iodide (F2) can antagonize myocardial ischemia/reperfusion (I/R) injury by blocking intracellular Ca2+ overload. The present study is to test the hypothesis that the protective effects of F2 on myocardial I/R injury is mediated by downregulating Egr-1 expression. Methods: The Sprague–Dawley rat myocardial I/R model and cardiomyocyte hypoxia/reoxygenation (H/R) model were established. With antisense Egr-1 oligodeox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 24 publications
(38 reference statements)
4
46
0
Order By: Relevance
“…As reported previously [13], FITC labeled Egr-1 AS-ODN was found in the cytoplasm and nuclei of myocardial tissues, while mainly in the nuclei of cultured cardiomyocytes (data not shown), indicating that Egr-1 AS-ODN had successfully been uptaken up.…”
Section: Uptake Of Egr-1 As-odn By Myocardial Tissues and Cultured Casupporting
confidence: 83%
See 4 more Smart Citations
“…As reported previously [13], FITC labeled Egr-1 AS-ODN was found in the cytoplasm and nuclei of myocardial tissues, while mainly in the nuclei of cultured cardiomyocytes (data not shown), indicating that Egr-1 AS-ODN had successfully been uptaken up.…”
Section: Uptake Of Egr-1 As-odn By Myocardial Tissues and Cultured Casupporting
confidence: 83%
“…In order to elucidate the cause-effect relationship between Egr-1 overexpression and myocardial I/R injury, we further studied the effects of Egr-1 AS-ODN on changes of enzymetic activities induced by I/R or H/R [13]. In above-mentioned study, we found that because of its direct inhibitory effect on Egr-1 protein Egr-1 phosphorothioate AS-ODN attenuated the myocardial I/R injury in cytomembrane structure as evidenced by the reduction of CK and LDH leakage, and in oxidative stress caused by reactive oxygen species (ROS) as evidenced by the increase of superoxide dismutase (SOD) activity and the decrease of malondialdehyde (MDA) yield [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations